Increased production of ADAMTS13 in hepatic stellate cells contributes to enhanced plasma ADAMTS13 activity in rat models of cholestasis and steatohepatitis - Watanabe, Naoko; Ikeda, Hitoshi; Kume, Yukio; Satoh, Yumiko; Kaneko, Makoto; Takai, Daiya; Tejima, Kazuaki; Nagamine, Masakazu; Mashima, Hirosato; Tomiya, Tomoaki; Noiri, Eisei; Omata, Masao; Matsumoto, Masanori; Fujimura, Yoshihiro; Yatomi, Yutaka (Thrombosis and Haemostasis, 2009)
Although hepatic stellate cells, endothelial cells, glomerular podocytes and plateles were reported to be a source of ADAMTS13, it is not clarified which source is involved in the regulation of plasma ADAMTS13 activity. It was demonstrated previously that selective hepatic stellate cell damage in rats caused decreased plasma ADAMTS13 activity.To further elucidate the potential contribution of hepatic stellate cells to the regulation of plasma ADAMTS13 activity, this study examined plasma ADAMTS13 activity when hepatic stellate cells proliferate during the process of liver fibrosis by employing rat models of liver fibrosis due to cholestasis, bile duct ligation, and steatohepatitis, a choline-deficient L-amino acid-defined-diet. ADAMTS13 expression was increased with co-localisation with smooth muscle α-actin, a marker of hepatic stellate cells, in bile duct-ligated livers up to four weeks, in which a close correlation between ADAMTS13 and smooth muscle α-actin mRNA expressions was determined. Plasma ADAMTS13 activity, measured by a sandwich ELISA involving a specific substrate to ADAMTS13, was increased in bile duct-ligated rats with a significant correlation with ADAMTS13 mRNA expression levels in the liver. Furthermore, ADAMTS13 mRNA expression was increased with enhanced mRNA expression in smooth muscle α-actin in the livers of rats fed a choline-deficient L-amino aciddefined-diet for 16 weeks, in which increased plasma ADAMTS13 activity was determined. Thus, increased plasma ADAMTS13 activity in cholestasis and steatohepatitis in rats may be due, at least in part, to enhanced ADAMTS13 production in the liver, suggesting a significant role of hepatic stellate cells in the regulation of plasma ADAMTS13 activity.
Keywords: ADAMTS13; hepatic stellate cell; smooth muscle α-actin; bile duct ligation; steatohepatitis